PENGARUH KEPRIBADIAN, ETIKA, DAN KEDISIPLINAN TERHADAP HASIL KINERJA PENGAJAR SMA - Alifia Agnes Purwanti (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2021)
The performance of an employee in the organization is certainly inseparable from the personality, abilities and motivation of the employee in carrying out his duties and work, of course, cannot be separated from the motivation that exists within the employee, the motivation of an employee will be seen from the activities he does in carrying out his duties and work. within the organization. Employing employees in outsourcing work bond status is now a strategic consideration for company owners or leaders, be it state-owned companies or privately-owned companies, the decision to hire employees with outsourced or permanent employees is one of the strategic policies for an organization.